Proses Terjadinya Sengketa antara Desa Pakan Dalam dengan Desa Paramaian Kecamatan Daha Utara Kabupaten Hulu Sungai Selatan, 2009-2021 - Ahmad Parhani; Rochgiyanti Rochgiyanti; Daud Yahya; Mohamad Zaenal Arifin Anis (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2023)
The land boundary dispute between Pakan Dalam Village and Paramaian Village was triggered duet o the issuance of an Oil Palm Plantation Right to use permit in Hulu Sungai Selatan Regency and occurred duet o the issuance of a Certificate of Land Ownership unilaterally by Paramaian Village on existing lands in Pakan Dalam Village and cause changes in the image on the map in the Central Bureau of Statistics book of Hulu Sungai Selatan Regency in 2009. The purpose of this study is to explain the process of dispute occurrence starting from the pre-conflict, confrontation, crisis, and post conflict periods from 2009-2021. This research uses the Historical Method which in writing goes through the heuristic stage, data is collected from interviews nd documents. Criticism is made to find out the veracity of the data. Interpretation is carried out to analyze the data. The las tis historiography, which is to write systematically based on chronological narratives. The results of the study, in 2009 were shown by changes in map image, in 2016 the Pakan Dalam Village goverment sent a letter to the Central Bureau of Statistics of Hulu Sungai Selatan Regency, in 2017 the peak of the dispute problem, in 2020 the problem began to subside, and in 2021 there was a peace agreement at the Daha Utara Subdistrict Office. The conclusion is the dispute occurred because of the existence of an Oil Palm Plantation Company, the dispute began in 2009 and ended in 2021 with an agreement to make village pegs at each coordinate point of each village.